Biomass based activated carbons for fuel cells. (October 2019) - Volperts, Aleksandrs; Plavniece, Ance; Dobele, Galina; Zhurinsh, Aivars; Kruusenberg, Ivar; Kaare, Kätlin; Locs, Janis; Tamasauskaite-Tamasiunaite, Loreta; Norkus, Eugenijus
Abstract: This study is devoted to wood and pulping residues based nitrogen doped nanoporous activated carbons for application as catalysts in fuel cells. Carbonaceous materials were obtained by thermochemical activation with NaOH, doping was performed using dicyandiamide. Changes of porous structure in the process of doping were studied and it was found that this treatment decreases porosity of activated carbons. Content of introduced nitrogen depended on the content of elemental oxygen in the structure of precursor. Electrocatalytic activity of activated and nitrogen doped wood char and black liquor was tested and was found to be comparable with commercial 20% Pt/C catalyst. The results of this study demonstrate that nitrogen doped activated carbons on the base of biomass are promising materials for application in fuel elements for oxygen reduction. Highlights: Activated carbons are obtained from biomass. Activated carbons are doped with nitrogen and studied. Promising materials for application in fuel elements for oxygen reduction. Effective, cheap and electrochemically active carbon materials for energy applications.